Promoting recycling in the solid waste management system of Cairo - Mostafa, Iman Mostafa Kamel (AUC Knowledge Fountain, 2016)
Waste management system in Cairo has been noticeably witnessing deterioration over the last fifteen years, where the entire chain of activities have deficiencies; including collection, transportation, recovery, and disposal systems. Although waste recycling is a vital element of a sustainable waste management system, as it contributes to benefiting the environment through the efficient use of resources, the society through creating job opportunities, and the economy through attracting new investments, in Egypt it is not included in the policy framework, and it is hardly a part of the formal system and is only performed by the informal sector. This thesis identifies the gaps in the existing legislative, institutional and financial frameworks of the Solid Waste Management (SWM) system in Egypt and specifically in Cairo, that hinder mainstreaming waste recycling in specific in the policy framework. It also finds win-win situations for the parties involved in the SWM sector that would promote the recycling activity. Finally, it proposes new ways for managing the different SWM activities (collection, transportation, recovery and disposal) that would lead to successful recycling practices. The result from this study indicates that the reasons why waste recycling is not promoted in Cairo are the lack of financial autonomy, deficiencies in the legislative and institutional setup, and weaknesses in the governance of the SWM process. Accordingly, policy recommendations are proposed in addition to a SWM initiative for Cairo that clarifies the roles of each stakeholder and reform the whole chain of activities of the SWM system of Cairo, through integrating the informal sector and encouraging the local private sector participation in a way that would promote waste recycling